Digitalisation in the WFP fresh food voucher programme: a pilot study from rural Amhara region, Ethiopia - Dad, Fazal; Dibari, Filippo; Kebede, Aweke; Lefu, Emma; Ndumiyana, Tafara; Butaumocho, Blessing (Frontiers in Nutrition, 2023)
Introduction Malnutrition continues to pose a major challenge to human well-being around the world. In Ethiopia, 39% of children <5 years are stunted, with peaks in northern regions of the country such as Amhara (54.8%). Very few (2%) children in the region achieve the minimum dietary diversity and only a minority (27%) belong to households that can afford a nutritious diet. To tackle the high stunting rate, diets high in fruits and vegetables are widely recommended to improve dietary diversity. Programmes leveraging fresh food vouchers can be used to support vulnerable groups with malnutrition and limited affordability. Cash-based transfer (CBT) programmes have repeatedly been shown to improve child growth and increase household food security and dietary diversity. This study is part of the World Food Programme (WFP) intervention regarding a stunting reduction rural programme of restricted CBT for improving dietary diversity in households with children under 2 years of age and pregnant and lactating women. Methods A community- based pilot study to assess the itemised foods purchased by beneficiaries was conducted in the four most accessible woredas of the Amhara region of Ethiopia. A total of 556 beneficiaries and 12 active retailers were selected randomly from 10 rural markets in the targeted woredas. A point of sale (POS) system was used to collect the itemised food prices and amounts of food procured by the beneficiaries. Results and Discussion Approximately 51, 35, and 15% of the beneficiaries purchased vegetables, fruits, and eggs, respectively. Prices, taste preferences of children, and shelf life determine the purchase of certain food items. The average food expenditure was 49 Ethiopian Birr (ETB; US 0.94), representing the 63 and 37% daily and monthly requirements, respectively, for affordability. The higher increase in prices of some food items might be due to their seasonality. Almost half of the Fresh Food Voucher (FFV) beneficiaries were purchasing and consuming vegetables. The finding indicates that the WFP fresh food voucher programme contributes 63% (49 ETB, US 0.94) and 37% (837 ETB, US 16.1) of the daily and monthly needs of affordability, respectively, for a diversified nutritious diet. The use of Unstructured Supplementary Service Data (USSD) technology in the WFP digital voucher under the Fresh Food Voucher (FFV) project was effective at collecting itemised prices of foods purchased by the beneficiaries. The point of sale (POS)1 system can be scaled up under the Fresh Food Voucher (FFV) programme so that the digital voucher can contain the itemised food prices. Timely data from the point of sale could be used for timely Social Behaviour Change Communication (SBCC) development to improve dietary diversity.